Determinants of knowledge management systems success in the banking industry - Cham, Tat Huei; Lim, Yet Mee; Cheng, Boon Liat *; Lee, T. H. (Emerald, 2016)
Purpose – This study aims to examine the impact from technical and social aspects on knowledge management system (KMS) success. Moreover, this study also attempts to examine the interrelationships between KMS success and user satisfaction. Design/methodology/approach – A questionnaire survey was used to collect data from the commercial bank officers to test the proposed KMS success model. All the measurement scales adopted in this study were adopted from the existing literature. The data collected in this study were analysed using both SPSS and structural equation modelling approach via AMOS. Findings – The research results indicate that both technical (knowledge quality, system quality and service quality) and social factors (user trust and management support) play a significant and positive role in system user satisfaction. The results also show that user satisfaction have a direct influence on the success of KMS and vice versa. Originality/value – This study is one of the few studies on KMS which include both the technical and social perspectives in examining KMS success. This research study raises the importance of social factors, which have been earlier neglected by many studies on KMS success models. Moreover, the interrelationships relationship between KMS success and user satisfaction also been examined in this study.